ANALISIS EFISIENSI TEKNIS USAHATANI PADI DI JAWA DAN LUAR JAWA : PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - Juni Hestina; Rita Nurmalina; Suharno Suharno (Forum Agribisnis, 2017)
Efficiency is an important aspect for farmer that can be used as a measuring tools to make a decision regarding production among available options. The objectives of this research is to evaluate the technical efficiency of paddy farming, and to identify the factors that influence the technical efficiency of paddyfarms in Jawa and outside Jawa. To analyzed the data, data envelopment analysis (DEA) approach and tobit regression were applied. Farmers were not use the the right amount of inputs as being recommended by the instructor, such as the use of seed, fertilizer NPK and urea. The use of Urea, NPK, and labor had the largest percentage of input slacks when compared to the other production inputs. Farmers in Jawa could reduce the use of urea by 6.75 kg, NPK by 14.96 kg, and labor by 7.45 HOK and farmers in outside Jawa could reduce the use of urea by 32.37 kg, NPK by 6.01 kg, and labor by 15.93 HOK  to make the paddy farm technically efficient. One of the factors that can greatly influence the improvement of farming technical efficiency is the socio-economic factors. Factors that affecting the technical efficiency of paddy farm in Jawa  were the age, the level of formal education, member of Farming group and the number of members in the household, and do not significantly affect the technical efficiency of paddy farm is acces formal finance, and ectention. Factors that affecting the technical efficiency of paddy farm in outside Jawa  were the age, the level of formal education, and member of Farming group and, and do not significantly affect the technical efficiency is the number of members in the household, acces formal finance, and ectention.